Learning technology for education in cloud : 4th International Workshop, LTEC 2015, Maribor, Slovenia, August 24-28, 2015, Proceedings /: 4th International Workshop, LTEC 2015, Maribor, Slovenia, August 24-28, 2015, Proceedings. (2015) - Unknown
No abstract available